DEIKSIS DALAM NOVEL "ASSALAMUALAIKUM BEIJING" KARYA ASMA NADIA (Suatu Kajian Pragmatik) - TOLOGANA, WALSET (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRAC The aims of this study is to identify, classify and analyze the types of deixis in the novel "Assalamulaikum Beijing" by Asma Nadia and explain why authors use deixis in the novel "Assalamulaikum Beijing". The method used in this study is a qualitative method using qualitative descriptive data and using the theory of Purwo (1983) and Putrayasa (2014). Analysis of the use of deixis in the dialogue contained in the novel, is divided into five sections: deixis persona, place deixis, time deixis, discourse deixis and social deixis.                Study pragmatic dialogue novel "Assalamualikum Beijing" by Asma Nadia Reviewing about deixis with the study of deixis first person (I, my, me), deixis second person (you, they), deixis third person (she, it), deixis first person to second person (us), deixis person first without the second person (we), second person is more than one (you), deixis third person more than one (they) deixis a locative (here, there), deixis place demonstrative ( this, it is), deixis of time (past, present, earlier), discourse deixis (this, that), social deixis (use a polite word). deixis is often used by authors and frequently appears in this research that deixis persona second category a total of 77 pieces, 74 pieces deixis third person and first person deixis 66 pieces. Keywords: Pragmatics, deixis, the novel "Assalamualaikum Beijing".